Advanced machine learning - Mason, Hilary (O'Reilly, 2012)
"In this sequel to 'An introduction to machine learning with web data', bit.ly lead scientist Hilary Mason shows you how to solve real-world problems with machine learning. Using real data from an actual ecommerce website, you will apply production quality algorithms to understand all the issues that arise when working in a live environment."--Resource description page.